Analysis of Leverage, Profitability and Interest Rate Ratio on Company Value With Size as an Intervening Variable - Mohamad Ibnussoim; Suyanto Suyanto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The Indonesia Stock Exchange (IDX) is a place for transactions of shares of companies that have met the requirements. The incident of the spread of Covid-19 has an impact on stock market instability which also has an impact on company value. Investors are cautious in investing in the IDX including considering the value of the company. According to a number of studies, firm value (PBV) is influenced by leverage (DER), profitability (ROE), interest rates (BI Rate), and company size (SIZE) but inconsistently (positively or negatively). There are other studies that show an inconsistent relationship between DER, ROE, BI Rate and SIZE. Therefore, it is necessary to analyze DER, ROE, and BI Rate on PBV with SIZE as an intervening variable. The research was conducted on companies listed in LQ45 for the 2019-2022 Period using purposive sampling method and based on their annual financial statements. Other data is obtained from the Central Bureau of Statistics, and Yahoo Finance. Data processing using SmartPLS with the PLS-SEM method with a 95% confidence level reinforced by the Sobel Test. The results of the study are based on direct influence, namely: 1) Leverage (DER) has a significant positive effect on firm value (PBV), 2) Profitability (ROE) has no effect on firm value (PBV), 3) Interest Rate (BI Rate) has no effect on firm value (PBV), 4) Firm size (SIZE) has a significant negative effect on firm value (PBV), 5) Leverage (DER) has a significant positive effect on firm size (SIZE ), 6) Profitability (ROE) has no effect on firm size (SIZE), 7) Interest rate (BI Rate) has no effect on company size (SIZE). Based on the indirect effect, the results are: 1) Leverage (DER) has a significant negative effect on firm value (PBV) through firm size (SIZE), 2) Profitability (ROE) has no effect on firm value (PBV) through firm size (SIZE), and 3) Interest rates (BI Rate) have no effect on firm value (PBV) through company size (SIZE). Based on this research, companies need to be wise in managing debt in connection with the significant positive leverage (debt) on firm value. Likewise, with the effect of profitability (ROE) on firm value negatively although not significant, companies need to anticipate/be careful because in real conditions profitability should have a positive effect on firm value. This anomalous condition can occur during Covid-19 and therefore companies must be wiser in running their business effectively and efficiently in order to achieve high profitability and firm value.